Synthetic virology: engineering viruses for gene delivery. (4th September 2014) - Guenther, Caitlin M.; Kuypers, Brianna E.; Lam, Michael T.; Robinson, Tawana M.; Zhao, Julia; Suh, Junghae
<x xml:space="preserve">Abstract</x> The success of gene therapy relies heavily on the performance of vectors that can effectively deliver transgenes to desired cell populations. As viruses have evolved to deliver genetic material into cells, a prolific area of research has emerged over the last several decades to leverage the innate properties of viruses as well as to engineer new features into them. Specifically, the field of synthetic virology aims to capitalize on knowledge accrued from fundamental virology research in order to design functionally enhanced gene delivery vectors. The enhanced viral vectors, or 'bionic' viruses, feature engineered components, or 'parts', that are natural (intrinsic to viruses or from other organisms) and synthetic (such as man‐made polymers or inorganic nanoparticles). Various design strategies—rational, combinatorial, and pseudo‐rational—have been pursued to create the hybrid viruses. The gene delivery vectors of the future will likely criss‐cross the boundaries between natural and synthetic domains to harness the unique strengths afforded by the various functional parts that can be grafted onto virus capsids. Such research endeavors will further expand and enable enhanced control over the functional capacity of these nanoscale devices for biomedicine. WIREs Nanomed Nanobiotechnol 2014, 6:548–558. doi: 10.1002/wnan.1287 For further resources related to this article, please visit the WIREs website. Conflict of interest: The authors declare no conflicts of interest.